VD_FINDINFO Décision / 2014 / 810 vom 25. September 2014 - VD Tribunal cantonal (2014)
RISQUE DE COLLUSION, RISQUE DE FUITE, PROPORTIONNALITÉ, PRINCIPE DE LA CÉLÉRITÉ | 212 al. 3 CPP (CH), 221 al. 1 let. a CPP (CH), 221 al. 1 let. b CPP (CH), 5 CPP (CH)